L’idée de science chez des enseignants en formation: Une analyse quantitative et qualitative à partir d’un test - Guilbert, Louise (Canadian Journal of Higher Education, 1992)
Over the last three decades, there has been renewed interest on the part of educators, researchers and associations devoted to science teaching, in understanding students' epistemological knowledge or, in other words, their beliefs about the nature of science, its way of constructing knowledge, its limits and its criteria. In spite of this international concern, little research has been devoted to investigating pre-service teachers' conceptions about science. In this experimental research, we investigate the conception of science among future high school and college teachers with a Bachelor of science degree. The literature review suggests that the teachers ' conception of science influences the students own conception which, in turn, can have an impact on students' learning strategies or on the way they see themselves as learners. This was our first pedagogical motivation in initiating this research; the second involved the importance for critical thinking in science, as a means of acquiring epistemological knowledge, in order to be able to step back and form a critical judgment on science-society interactions. To investigate the conception of science among our future science teachers, we chose the "Test On Understanding Science" (TOUS), already translated into French, which, however, had to be modified and validated. The results were analysed in a usual quantitative fashion but also in a new qualitative way where the choice of items, adequate or not, were considered in order to reconstruct the conception of science of pre-service teachers. As a whole, the quantitative results obtained seem to indicate better understanding of tactics and strategies used in science and how scientists are as persons, rather than the intrinsic nature of science and its aim. From the qualitative analysis, we can infer that for nearly a third of pre-service teachers: the facts in themselves are a kind of scientific knowledge, and the gathering of facts appears the aim of science and not just a means toward an end. In our sample, we find empiricist and constructivist perspectives about science but, surprisingly, it seems that almost half of the subjects change their perspective depending on the aspect of science considered. Is this indicative of a possible ongoing conceptual change?